Ovarian mesonephric-like adenocarcinoma arising in serous borderline tumor: a case report with complex morphological and molecular analysis - Dundr, Pavel; Gregová, Mária; Němejcová, Kristýna; Bártů, Michaela; Hájková, Nikola; Hojný, Jan; Stružinská, Ivana; Fischerová, Daniela (Diagnostic pathology, 2020)
BACKGROUND: Mesonephric-like adenocarcinoma (M-LAC) is a rare, recently described tumor occurring in the uterine corpus and ovary, which shares the same morphological and immunohistochemical features with the more common mesonephric adenocarcinoma (MAC), which mostly arises the uterine cervix. Despite the similarities between these tumors, the histogenesis of M-LAC is still disputable. CASE PRESENTATION: Sixty-one-year-old woman presented with an advanced tumor of the left ovary with intraabdominal spread and liver metastases. After receiving 5 cycles of neoadjuvant chemotherapy, she underwent a hysterectomy with bilateral salpingo-oophorectomy, and resection of the liver metastasis, omentum, and appendix. Histologically, the ovarian tumor consisted of two components, whose morphology and immunohistochemical results were typical of either a serous borderline tumor (immunohistochemical positivity for PAX8, WT1, ER and PR) or a mesonephric-like carcinoma (immunohistochemical positivity for PAX8, TTF1 and GATA3). Only the component of the mesonephric-like adenocarcinoma metastasized to the omentum and liver. A molecular analysis with a panel of 271 genes (size 1020 kbp) was performed separately on samples from the borderline tumor, primary ovarian mesonephric-like adenocarcinoma, and liver metastasis. The results showed the clonal origin of all samples, which shared the same KRAS (NM_004985.3:c.34G > T, p.(G12C)) and PIK3CA (NM_006218.2:c.1633G > A, p.(E545K)) somatic mutations. Moreover, in the sample from the primary mesonephric-like carcinoma and its liver metastasis a likely pathogenic somatic MYCN mutation (NM_005378.4:c.131C > T, p.(P44L) was found. In all samples, the deletion of exons 9-10 in the CHEK2 gene was present, which is in concordance with the previously performed genetic testing of the blood specimen which revealed the hereditary CHEK2 mutation in this patient. CONCLUSIONS: Our result support the theory that at least some mesonephric-like ovarian adenocarcinomas are of Müllerian origin. The serous borderline tumor seems to be a precursor of mesonephric-like adenocarcinoma, which has been proven in our case by both tumors sharing the same mutations, and the presence of cumulative molecular aberrations in the mesonephric-like adenocarcinoma.
Keywords: Adenocarcinoma; nádory dělohy; prekancerózy; Humans; lidé středního věku; Biomarkers, Tumor; Female; nádory vaječníků; Ovarian Neoplasms; Mesonephric-like adenocarcinoma; lidé; Mesonephroma; mezonefrom; Uterine Neoplasms; nádorové biomarkery; ženské pohlaví; Precancerous Conditions; Middle Aged; serózní cystadenom; ovarium; Serous borderline tumor; adenokarcinom; Cystadenoma, Serous; Ovary; Case report